Gravimetric Estimation of Caffeine in Different Commercial Kinds of Tea Found in the Iraqi Market - Maha N. Hamad; Dhuha A. Abdul-Hussain (College of Pharmacy University of Baghdad, 2017)
Caffeine (1,3,7-trimethylxanthine), which is the most widely consumed stimulant in the world, had been isolated and estimated gravimetrically in fifteen  different commercial kinds of tea found in the Iraqi market.The kinds of tea were chosen according to their differences in the degree of fermentation and the method of processing i.e. black , gray and  green . The isolated caffeine was identified by melting point, sublimation, TLC, chemical tests, UV , IR , HPLC and CHNO analysis.                                                                                                               Key words: Caffeine, Purine, tea.